Trajetos da violência, da segurança pública e da sociedade civil na cidade do Rio de Janeiro - Leilah Landim; Raíza Siqueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This article seeks to contribute to the thinking on civil society organizations whose work deals primarily with urban violence and public security in the city of Rio de Janeiro, with special attention paid to the particularities of their creation, actuation, and organization. In discussing the trajectories, representations, and social practices constituting their operations over the last 30 years, the authors highlight continuities, discontinuities and articulations between non-governmental organizations (NGOs) working with rights, collective identities and social movements, as well as their relationships with the governmental apparatus. It also examines shifts in the ecology of civil society that stem from situations of violence, including the emergence of new political discourses and figures on the margins who are subject to extra-legal actions carried out by law enforcement agents. The groups and agents circulating between small collectives mobilized around the fragmented nature of the city are the closest witnesses to these everyday situations of exception. They are actors who have inserted themselves into the field of politics and must dispute their legitimacy through situations and relational dynamics occurring in the context of a pre-existing organizational landscape. Finally, the article identifies several characteristics of the (slow) construction of participatory mechanisms in public policy, and more specifically, public security. The study of civil society organizations and social movements related to urban violence in Rio de Janeiro today can contribute to better understandings of how these spaces function.
Keywords: Z18; 330; civil society organizations; city councils; public security; urban violence